The Business Judgment Rule in Corporate Law: A Comparative Study of Indonesia and Singapore - Gaol, Selamat Lumban (UNISSULA, 2025)
The Business Judgement Rule (BJR) is a fundamental doctrine in corporate governance that provides directors with protection when making informed, good-faith business decisions, while maintaining accountability to shareholders. As jurisdictions develop distinct approaches to balancing managerial discretion and oversight, differences in BJR application significantly influence legal certainty, director liability, and shareholder protection. This study aims to compare BJR implementation in Indonesia and Singapore, focusing on legal frameworks, judicial interpretations, and their implications for corporate governance effectiveness. Using a normative juridical method with a comparative law approach, the analysis reveals Singapore’s robust BJR framework, supported by clear jurisprudence and strong governance practices that consistently protect prudent directors. Conversely, Indonesia faces challenges due to the absence of explicit BJR codification in the Limited Liability Companies Act and inconsistent judicial interpretations, leading to uncertainty in determining director responsibility. These contrasts arise from differing legal traditions and regulatory structures. The study concludes that Indonesia should strengthen its regulatory framework and promote judicial consistency to enhance the role of BJR in ensuring good corporate governance and balancing director responsibilities with shareholder rights.